EFFECTIVENESS OF THE PSYCHOORGANIC ANALYSIS IN THE TRAIT ANXIETY REDUCTION - Brants, Armands; Poudžiunas, Inta; Pīlēna, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of study is to determine the possibility to reduce the level of anxiety as personality trait in the time of 22- month-long psychotherapeutic and educational group with using concepts of psychoorganic analysis – a relatively new branch of psychotherapy. The following concepts are used. Three relation forms: the unary form include a symbiotic relation level (undifferentiated sense of existence), the dual form is the binary and dialogic relation (“I am –YOU are”), the ternary form means the relation what is including a structure and the presence of the THIRD. The analysis and the evolution of three forms help to make sense of obstructive psychic occurrences in person. These occurrences are basis for life contracts, which have been protectively, but become troublesome in the lifetime. An activation of a micro–macro regulation is important in order the transformation of these occurrences. The evolution of three forms are the background for biodynamic work and the appropriate transformative intervention. The work of groups (36 participants in 2 groups) is managed from 8 psychotherapists and it is done following set instructions. Changes were evaluated 6 times with State-Trait Anxiety Inventory. The results show statistically significant reduction of the level of the trait anxiety of STAI-Y (p<.05) related to the group program and dynamic.